2011
DOI: 10.1186/1476-069x-10-7
|View full text |Cite
|
Sign up to set email alerts
|

The association of remotely-sensed outdoor temperature with blood pressure levels in REGARDS: a cross-sectional study of a large, national cohort of African-American and white participants

Abstract: BackgroundEvidence is mounting regarding the clinically significant effect of temperature on blood pressure.MethodsIn this cross-sectional study the authors obtained minimum and maximum temperatures and their respective previous week variances at the geographic locations of the self-reported residences of 26,018 participants from a national cohort of blacks and whites, aged 45+. Linear regression of data from 20,623 participants was used in final multivariable models to determine if these temperature measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…33,34 Our analysis extends previous findings on outdoor temperature and blood pressure, which consistently found lower SBPs and DBPs with higher outdoor temperatures. [10][11][12][13] Similarly, results from seasonality studies reported higher blood pressure values in cold winters compared with hot summers. [15][16][17][18][19][20][21] The association between outdoor temperature and blood pressure found in the present study was independent of Hb and vice versa.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…33,34 Our analysis extends previous findings on outdoor temperature and blood pressure, which consistently found lower SBPs and DBPs with higher outdoor temperatures. [10][11][12][13] Similarly, results from seasonality studies reported higher blood pressure values in cold winters compared with hot summers. [15][16][17][18][19][20][21] The association between outdoor temperature and blood pressure found in the present study was independent of Hb and vice versa.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, high daily temperatures coincided with lower systolic (SBP) and diastolic (DBP) blood pressure. [10][11][12][13][14] Moreover, during a cold winter, blood pressures were significantly higher than in a hot summer. [15][16][17][18][19][20][21] In addition to temperature, it has been suggested that other climate parameters like humidity are related to blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,14,17,18 Only few studies investigated the influence of season on BP adjusted for temperature 11,13 or conversely adjusted the influence of temperature for season. 32,33 Madsen and Nafstad 13 reported that in 18 770 Oslo citizens, office BP was highest in winter, but that adjustment for temperature removed the significance of this finding. Generally, daily temperature reflects the short-term variation in environmental BP cues, whereas season stands for the medium-to-long-term variation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] An inverse association between ambient temperature and BP has been observed in several studies.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] An inverse association between ambient temperature and BP has been observed in several studies.7-9 Thermoregulatory vasoconstriction, which increases arterial BP significantly, 10 is an adaptive response to provide enhanced circulatory function for the protective mechanisms that are activated to maintain temperature in cold weather (nonshivering thermogenesis and increased metabolic rate). …”
mentioning
confidence: 99%